2007
DOI: 10.1017/s1751731107000845
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous emissions during the fattening of pigs kept either on fully slatted floors or on straw flow

Abstract: The aim of this study was to compare the environmental impact of the straw-flow system for fattening pigs with the slattedfloor system by measuring pollutant gas emissions such as ammonia (NH 3 ), nitrous oxide (N 2 O), methane (CH 4 ) and carbon dioxide (CO 2 ), manure nitrogen (N) content and emissions of water vapour (H 2 O). Three successive batches of 32 pigs were fattened. For each batch, pigs were allotted to two groups raised in separated rooms fitted either with a concrete totally slatted-floor system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…This could lead to a more aerated litter with longer straw wisps, which limits N 2 O production. Bedded systems can lead to greater N 2 O emissions thanks to the heterogeneous environment combining aerobic and anaerobic microsites that promote its synthesis (Philippe et al, 2007a(Philippe et al, , 2007b(Philippe et al, and 2012. The emission factors obtained here correspond to the levels usually measured with slatted floor systems.…”
Section: Nitrous Oxidesupporting
confidence: 78%
“…This could lead to a more aerated litter with longer straw wisps, which limits N 2 O production. Bedded systems can lead to greater N 2 O emissions thanks to the heterogeneous environment combining aerobic and anaerobic microsites that promote its synthesis (Philippe et al, 2007a(Philippe et al, , 2007b(Philippe et al, and 2012. The emission factors obtained here correspond to the levels usually measured with slatted floor systems.…”
Section: Nitrous Oxidesupporting
confidence: 78%
“…Neither temperature nor size of operation was significant. The emissions were compared Osada et ú., 1998Nick et al, 2005Amon et al^007 Jdinàetal.,2007Pfiilippeaal., 2007aPhilippe a al., 2007bCosta and Guarino, 2008GiiariiioetaI,2O08 CabaratK et al, 2009Costa and Guatino, 2009Dourmad et al, 2009Paikovicova et al, 2009 Summary of swine buildings with pit ^"stems (95% CI) Nick et a]., 2004 Philippe tí al., 2007bBlanes-Mdal et al, 2008Cabaraux el al, 2009Dourmad et al, 2009Philippe Ö al., 2009Philippe et al, 2010 Siiinmar>' of swine buildings with bedded systems (95% CI) Amon et al .,2007Philippe et al, 2007a Summary of svvine buildings with straw flow systems (95% CI) Loyon « al, 2007 O\'a-all(95%CI) NjO emission factors on a per head per year basis. Farrowing swine had the greatest CH4 emissions whereas gestating swine had the greatest NjO emissions.…”
Section: Overall Analysis Of Variation In Greenhouse Gas Emissions Acmentioning
confidence: 99%
“…Besides, the present results showed that, although diet characteristics, feed intakes, animal performances and climate conditions are similar for both groups, CO 2 -emissions may differ because of housing conditions. Former experiments carried out with weaning and fattening pigs reached to the same conclusion (Philippe et al, 2007a and2007b;Cabaraux et al, 2009). Therefore, ignore CO 2 for the CO 2 eq calculation and thus for the GWP evaluation of livestock farming systems may be debatable.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, according to IPCC guidelines (IPCC, 2006), CO 2 emissions from livestock are not estimated. However, experiments carried out with weaning and fattening pigs (Philippe et al, 2007a and2007b;Cabaraux et al, 2009) showed that CO 2 -emissions might differ in relation to housing conditions while diet characteristics, feed intakes, animal performances, and climate conditions were similar. The study of CO 2 production from livestock buildings is also important because reference emissions factors are needed for ventilation rate estimation by mass balance method that is particularly used for naturally ventilated buildings (Pedersen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%